Clinically applicable magnetic-labeling of natural killer cells for MRI of transcatheter delivery to liver tumors: preclinical validation for clinical translation. (June 2015) - Li, Kangan; Gordon, Andrew C; Zheng, Linfeng; Li, Weiguo; Guo, Yang; Sun, Jing; Zhang, Guixiang; Han, Guohong; Larson, Andrew C; Zhang, Zhuoli
Aim: To test the hypothesis that MRI can monitor intraportal vein (IPV) transcatheter delivery of clinically applicable heparin-protamine-ferumoxytol (HPF) nanocomplex-labeled natural killer (NK) cells to liver tumor.Materials & methods: Liver tumor rat models underwent catheterization for IPV infusion of HPF-labeled NK cells (NK-92MI cell line). MRI measurements within tumor and adjacent liver tissues were compared pre- and post-NK cell infusion. Histology studies were used to identify NK cells in the target tumors.Results: For first time, we demonstrated that MRI tracks HPF-labeled NK cells migration within liver following IPV delivery.Conclusion: IPV transcatheter infusion permitted selective delivery of NK cells to liver tissues and MRI allowed tracking NK cell biodistributions within the tumors.